Electromagnetic Theory from Standpoint of the General Theory of Relativity in - Space (Global Journal of Science Frontier Research, 2017)
In this article we consider a long standing problem concerning of unification of electromagnetic and gravitational field concepts under single geometrical point of view. We discussed possibilities of obtaining of Maxwell’s equations from the equations of unified field theory in Y n - space. This equation we derived from the variation principle of least action in Y n space and they are the analog of Einstein-Hilbert equation in Y n - space. We present the theory that unifies electromagnetic and gravitational interactions.
Keywords: electromagnetism; gravitation; torsion; connection; field equations